A large predatory reef fish species moderates feeding and activity patterns in response to seasonal and latitudinal temperature variation. Issue 1 (December 2017) - Scott, Molly; Heupel, Michelle; Tobin, Andrew; Pratchett, Morgan
Abstract Climate-driven increases in ocean temperatures are expected to affect the metabolic requirements of marine species substantially. To mitigate the impacts of increasing temperatures in the short-term, it may be necessary for ectothermic organisms to alter their foraging behaviour and activity. Herein, we investigate seasonal variation in foraging behaviour and activity of latitudinally distinct populations of a large coral reef predator, the common coral trout, Plectropomus leopardus, from the Great Barrier Reef, Australia.P. leopardus exhibited increased foraging frequency in summer versus winter time, irrespective of latitude, however, foraging frequency substantially declined at water temperatures >30 °C. Foraging frequency also decreased with body size but there was no interaction with temperature. Activity patterns were directly correlated with water temperature; during summer, the low-latitude population ofP. leopardus spent up to 62% of their time inactive, compared with 43% for the high-latitude population. The impact of water temperature on activity patterns was greatest for larger individuals. These results show thatP. leopardus moderate their foraging behaviour and activity according to changes in ambient temperatures. It seems likely that increasing ocean temperatures may impose significant constraints on the capacity of large-bodied fishes to obtain sufficient prey resources while simultaneously conserving energy.